Analysis of Land Suitability for Sustainable Corn Crops in Indramayu District - Khaerul Muttaqien (LPPM Institut Studi Islam Sunan Doe, 2024)
Indramayu Regency has a land area of 209,942 ha, consisting of 115,897 ha of paddy fields, 56,937 ha of non-paddy fields, and 37,108 ha of non-agricultural land. However, in the use of agricultural land, farmers in Indramayu Regency still need direction in the proper use of land for corn crops. Because the average farmer in Indramayu has not paid attention to land suitability and government policies regarding land suitability for corn commodities. The method used in this study is a quantitative descriptive method and uses a matching process (matching) data on the condition of the area with the criteria for land suitability classes compiled using Arc GIS 10.3. The parameters observed were regional characteristics (climate, soil fertility and topography) and criteria for sustainable agriculture (availability of water in the form of rainfall) for maize. The purpose of this research was to determine the suitability of land and the sustainability of corn farming in Indramayu Regency. The results of the analysis of the suitability class of sustainable maize plants in Indramayu Regency with predetermined criteria, obtained results with a very suitable land area (S1) of 0 ha, quite suitable (S2) 89,106 ha, marginally suitable (S3) 26,791 ha not according to (N) an area of 0 ha.